1994
DOI: 10.1136/oem.51.10.674
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Sardinian lead and zinc miners: 1960-88.

Abstract: The mortality of 4740 male workers of two lead and zinc mines was followed up from 1960 for subjects employed 26 years, was, however, found among underground workers in mine A who on the average experienced an exposure to radon daughters 10-fold higher than those of mine B. By contrast, despite their higher exposure to silica, mine B underground workers experienced a lower than expected lung cancer mortality. A ninefold increase in risk of peritoneal and retroperitoneal cancer combined was also found among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 30 publications
(19 reference statements)
0
16
0
1
Order By: Relevance
“…Misdiagnosis of lung cancer on the death certificates might have prevented the detection of such an association while contributing at the same time to an increase in the SMR for ill-defined causes. However, in an earlier follow-up study of 2 lead and zinc mines located in the vicinity of the smelting plant, we found that lung cancer risk was increased among the miners whose silica exposure and risk of pneumoconiosis were lower, but for whom the levels of radon daughters were measurable, while no excess risk of lung cancer was found among the miners whose silica exposure and the risk of pneumoconiosis were very high, but for whom the radon-daughter levels were negligible (9). On the other hand, in this study, the Poisson regression analysis showed that the risk of pneumoconiosis and lung cancer followed parallel curves by duration of employment, with small increases up to 20 years of employment and a decrease thereafter, when cohort members employed 1-10 years were used as the internal reference.…”
Section: Discussionmentioning
confidence: 92%
“…Misdiagnosis of lung cancer on the death certificates might have prevented the detection of such an association while contributing at the same time to an increase in the SMR for ill-defined causes. However, in an earlier follow-up study of 2 lead and zinc mines located in the vicinity of the smelting plant, we found that lung cancer risk was increased among the miners whose silica exposure and risk of pneumoconiosis were lower, but for whom the levels of radon daughters were measurable, while no excess risk of lung cancer was found among the miners whose silica exposure and the risk of pneumoconiosis were very high, but for whom the radon-daughter levels were negligible (9). On the other hand, in this study, the Poisson regression analysis showed that the risk of pneumoconiosis and lung cancer followed parallel curves by duration of employment, with small increases up to 20 years of employment and a decrease thereafter, when cohort members employed 1-10 years were used as the internal reference.…”
Section: Discussionmentioning
confidence: 92%
“…Eighteen studies from the United States (Cooper et al 1985; Michaels et al 1991; Robinson 1974; Sheffet et al 1982; Steenland et al 1992; Tollestrup et al 1995), Europe (Alexieva et al 1981; Belli et al 1989; Carta et al 2003; Cocco et al 1997, 1994; Davies 1984; Dingwall-Fordyce and Lane 1963; Gerhardsson et al 1995; Lundstrom et al 1997; Malcolm 1971; Wilczynska et al 1998), and Australia (McMichael and Johnson 1982) met our inclusion criteria (Table 3). Battery, ceramic, pigment, refinery, and smelter industries were studied.…”
Section: Resultsmentioning
confidence: 99%
“…A case-control study by Blot et al [6], which compared individuals who are Zn sufficient to those who have Zn overload, found a positive association between occupational Zn exposure and risk. In contrast, Cocco et al [139], in a prospective study of 4,740 lead and Zn smelter workers in Italy, found no association between lung cancer mortality and airborne Zn concentrations as assessed using regular measurements of airborne dust from personal and static sampling devices.…”
Section: Zincmentioning
confidence: 87%